The genotyping of human leukocyte antigens C (HLA-C) in psoriasis patients. - احمد, رنا; هيثم يازجي; فيصل رضوان; فوز حسن (Latakia University Journal -Medical Sciences Series, 2024)
Background: Psoriasis is a complex skin disease with a genetic immunological background, with the dominance of MHC region genes as one of a group of factors that intervene in the pathogenetic mechanism and predict therapeutic response. Aim: To identify human leukocyte antigen C alleles in psoriasis patients compared to healthy individuals. Materials and Methods: Fifty psoriasis patients with or without arthritis were compared with thirty people without psoriasis and without a family history of psoriasis. They were randomly selected and considered as controls. Their HLA-C alleles were determined by PCR-SSP. Results: Out of 50 chronic psoriasis patients; the number was 13 male patients (26%) and 37 female patients (74%), with the average age of the patients being 40.42±17.62 years. There were 30 control cases, including 12 male patients (40%) and 18 female patients (60%), with an average age of 40.42 ± 17.62 years. A positive family history was recorded in 18.7% of the patients. 74% of psoriasis cases were of the early type, with a mean age of disease onset of 29.04±15.6 years. The most common clinical phenotype was plaque psoriasis diagnosed in 80% of cases, followed by pustular psoriasis and guttate psoriasis; 12% and 8%, respectively. 24 of 50 patients (48%) had mild disease according to the PASI score. The HLA-C*06 allele was more common in psoriasis patients compared to the control group (42% in the patients' group, 16.7% in the control group with a statistically significant difference (p-value = 0.02), with a higher risk of developing psoriasis (odds ratios OR [CI95%] = 3.6[1.1-11.01]), while *03 was considered a protective allele against psoriasis. Conclusion: The importance of the HLA-C*06 allele as a primary risk factor for psoriasis in the Syrian population has been noted. Therefore, early genotyping of patients’ first- or second-degree relatives is recommended to detect its presence in them and apply preventive measures that limit the early appearance of the disease.